Role of preoperative sublingual misoprostol in reducing need of analgesia and anaesthesia for gynaecological procedures in rural hospital - Gupta, Shaveta; Acharya, Neema; Hariharan, C.; Batra, Sunaina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Many of gynaecological procedures require dilatation of cervix which may cause complications like excessive pain, cervical damage, creation of false tract and uterine perforation. Most of these may be done as outpatient procedures, which may reduce anaesthetic complications and decrease hospital stay. Misoprostol is a prostaglandin E1 which is proven to be effective in cervical priming hence reducing the fore mentioned complications. Methods: The study was randomized control trial followed a single bind style for two parallel groups. There were two groups, study group (n=100) and control group (n=100). The patients were recruited from the indoor as well as OPD requiring intrauterine procedure (viz D&C, hysteroscopy, HSG). The women of misoprostol group received, 200 microgram of misoprostol sublingualy and the women of placebo group received l mg folic acid 2 hours prior to the intrauterine procedure. Cervical dilatation, time required for the dilatation, cervical resistance, general experience of the patient, side effects, need of anaesthesia and complications were studied. Results: In present study mean post drug cervical dilatation was 4.08 ± 0.88 in study group which was more than control group 2.08 ± 0.27. It was statistically significant by using student‘t’ test as p value <0.05. It was found that preoperative cervical dilatation was mostly equal in both study group and control group. In the present study it was found that mean time required for cervical dilatation was 36.00 ± 11.19 in study group which was less than in control group 75.50 ± 7.43. It was statistically significant by using ‘t’ test as p value <0.05. Cervical dilatation was required in 25% women in study group and 100% in control group. Anaesthesia was required in 25% women in study group and 100% in control group. Side effects regarding bleeding after post drug cervical dilatation in study group were statistically different as compared to control group. No complications were present in present study. Conclusions: Misoprostol PGE1 is commercially widely available, safe and cost effective drug which can be used as a cervical ripening/priming agent before all the gynaecological procedures in non-pregnant women as it increases the cervical dilatation and decreases the need of analgesia or anaesthesia.